Combining genetic analyses of archived specimens with distribution modelling to explain the anomalous distribution of the rare lichen Staurolemma omphalarioides: long‐distance dispersal or vicariance?. (26th May 2014) - Bendiksby, Mika; Mazzoni, Sabrina; Jørgensen, Marte H.; Halvorsen, Rune; Holien, Håkon; Pearman, Peter
Abstract Aim The rare lichen species Staurolemma omphalarioides is known mainly from the lowlands and coastal areas of the Mediterranean region but has also been found in coastal parts of central Norway. Despite extensive search efforts by experts for more than half a century, the species has been found nowhere in the gap. Our aim is to identify the most plausible explanation for this anomalous distribution by combining genetic analysis of archived specimens with distribution modelling. Location Europe, western Middle East and North Africa (but mainly the Mediterranean and Atlantic floristic regions). Methods We used multi‐locus DNA sequencing of archived specimens and phylogenetic and network analyses to reveal potential genetic lineages within S. omphalarioides. We used georeferenced specimens and bioclimatic variables to model the distributions of the species and two genetic lineages, and to find the main environmental correlates of the distributions. Results Our phylogeographical results show that S. omphalarioides contains genetic variation that correlates with geographical distance, although with a few shared haplotypes across disjunct ranges. Distributions of the species as well as the two genetic lineages are non‐random. Distribution models predict occurrences of the species as well as one of its genetic lineages outside the current range of the species. Main conclusions Our results indicate that neither the species nor its component genetic lineages have reached their potential distributions. Shared haplotypes across disjunct distributions, and absence from regions with suitable refugial habitats along the Atlantic coast of Western Europe, support long‐distance dispersal, rather than vicariance, as the primary cause for the current distribution of the species.